Super cool science : South Pole stations, past, present, and future - Markle, Sandra. frey50 (New York : Walker, 1998)
Text and photographs tell the story of science research stations at the South Pole, including the one currently under construction which will launch a new era of science.
Keywords: Laboratories -- South Pole; Research; South Pole; Antarctica -- South Pole; Juvenile works